Learning to resuscitate at school. Study in 8-12 year-old schoolchildren - Santiago Martínez-Isasi; Cristian Abelairas-Gómez; María Pichel-López; Roberto Barcala-Furelos; Cristina Varela-Casal; David Vázquez-Santamariña; Luis Sánchez-Santos; Antonio Rodríguez-Núñez (Elsevier, 2022)
Objective: To quantitatively assess the learning capacity of school children aged between 8-12 years in basic life support (theory and practice) after a feasible school training programme. Material and methods: Quasi-experimental study with a convenience sample of 567 pupils in 3rd and 5th year of Primary Education, and first year of Compulsory Secondary Education, from 3 public schools in Galicia. They received 2h (one theoretical and another practical) of basic life support training by their Physical Education teachers, as part of the school program. The children were evaluated by a theoretical test and a practical skill test that measured the quality of chest compressions, and assessed the performance of the basic life support sequence. Results: The level of knowledge increased with respect to the baseline, and was higher in the higher grades (P < .001). The complete basic life support sequence was carried out by 16.5% of pupils in the 3rd year of Primary Education, 54.4% of pupils in the 5th year of Primary Education, and 28.5% of pupils in the 1st year of Secondary Education (P = .030). The following compression quality parameters improved significantly with age: continuity of compressions (P < .001), percentage of compressions performed at correct depth (P = .002), and median depth (P < .001), while the percentage of compressions with correct decompression decreased significantly (P < .001). Conclusions: Although their anthropometric characteristics may not allow them to achieve the ideal quality of this manoeuvre, a 2h theoretical and practical training programme, taught by Physical Education teachers, helps to improve the ability of children younger than 13 years old to recognise the emergency, start the chain of survival, and initiate chest compressions. Resumen: Objetivo: Valorar cuantitativamente la capacidad de aprendizaje en soporte vital básico (teórica y práctica) de escolares de 8-12 años con un programa de formación adaptado a las escuelas. Material y métodos: Estudio cuasiexperimental con una muestra de conveniencia de 567 alumnos de 3° y 5° de Educación Primaria y 1° de Educación Secundaria Obligatoria, de 3 colegios concertados de Galicia, que recibieron 2 h (una teórica y otra práctica) de formación en soporte vital básico por parte de sus profesores de Educación Física integrada en el programa escolar. Los niños fueron evaluados mediante un test teórico y una prueba práctica que midió la calidad de las compresiones torácicas y valoró la secuencia de soporte vital básico. Resultados: El nivel de conocimientos aumentó respecto al basal y fue mayor en los alumnos de cursos superiores (p < 0,001). La secuencia completa de soporte vital básico fue realizada por el 16,5% de los escolares de 3° de Educación Primaria, el 54,4% de los de 5° de Educación Primaria y el 28,5% de los de 1° de Educación Secundaria Obligatoria (p = 0,030). Los siguientes parámetros de calidad de las compresiones mejoraron de forma significativa con la edad: continuidad de las compresiones (p < 0,001), porcentaje de compresiones realizadas con una profundidad correcta (p = 0,002) y mediana de profundidad (p < 0,001), mientras que el porcentaje de compresiones con descompresión correcta descendió significativamente (p < 0,001). Conclusiones: Un programa formativo teórico-práctico de 2 h, impartido por los profesores de Educación Física, contribuye a mejorar la capacidad de los niños menores de 13 años para reconocer la emergencia, poner en marcha la cadena de supervivencia e iniciar las compresiones torácicas, aunque posiblemente sus características antropométricas no les permitan alcanzar la calidad ideal establecida para esta maniobra.